Compacted N‐Doped 3D Bicontinuous Nanoporous Graphene/Carbon Nanotubes@Ni‐Doped MnO2 Electrode for Ultrahigh Volumetric Performance All‐Solid‐State Supercapacitors at Wide Temperature Range. Issue 33 (24th July 2022) - Qin, Kaiqiang; Baucom, Jesse; Diao, Lechen; Lu, Yunfeng; Zhao, Naiqin
Abstract: Developing wide temperature range flexible solid‐state supercapacitors with high volumetric energy density is highly desirable to meet the demands of the rapidly developing field of miniature consumer electronic devices and promote their widespread adoption. Herein, high‐quality dense N‐doped 3D porous graphene/carbon nanotube (N‐3DG/CNTs) hybrid films are prepared and used as the substrate for the growth of Ni‐doped MnO2 (Ni‐MnO2 ). The integrated and interconnected architecture endows N‐3DG/CNTs@Ni‐MnO2 composite electrodes' high conductivity and fast ion/electron transport pathway. Subsequently, 2.4 V solid‐state supercapacitors are fabricated based on compacted N‐3DG/CNTs@Ni‐MnO2 positive electrodes, which exhibit an ultrahigh volumetric energy density of 78.88 mWh cm ‐3 based on the entire device including electrodes, solid‐state electrolyte, and packing films, excellent cycling stability up to 10 000 cycles, and a wide operating temperature range from −20 to 70 °C. This work demonstrates a design of flexible solid‐state supercapacitors with exceptional volumetric performance capable of operation under extreme conditions. Abstract : 2.4 V solid‐state supercapacitors are fabricated based on compacted N‐3DG/CNTs@Ni‐MnO2 positive electrodes, which exhibit an ultrahigh volumetric energy density of 78.88 mWh cm –3 based on the entire device including electrodes, solid‐state electrolyte and packing films, excellent cycling stability up to 10 000 cycles, and a wide operating temperature range from −20 to 70 °C.